Fabricating Tools and Training on Making Fertilizer from Household Organic Waste for PKK Women RT 15 RW 11, Banjararum Village, Singosari District, Malang Regency - Lisa Agustriyana; Subagiyo Subagiyo; Zakki Fuadi Emzain; Nurchajat Nurchajat; Eko Yudianto (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
Household waste has the potential to generate economic value. One of the benefits is that organic waste can be managed and turned into organic fertilizer. The women of PKK RT 15/ RW 11, Banjararum Village, Singosari District, Malang Regency have problems that organic waste has not been managed and have toga plants that require compost for treatment. This community service activity aims to provide organic waste chopper and to train skills in making organic fertilizers by empowering PKK women. The stages carried out in service activities were surveys, coordination, tool making, training, and evaluation. The service implementation results showed that the organic waste chopper worked correctly and produced a small size of waste. The training on making organic fertilizer with a mixture of local micro-organisms (MOL) was done successfully, and PKK women participated enthusiastically. With this service activity, residents of RT 15 and PKK women can manage organic waste well and produce organic fertilizer for the needs of toga plants and can be sold to other residents.